A tetragonal barium titanate powder, a preparation method and application thereof
Patent Information
- Application Number
- CN202611401444.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-30
AI Technical Summary
本申请以纳米级锐钛矿型二氧化钛为钛源,在无需额外添加矿化剂的条件下,通过与钡源进行一次球磨混合、分段煅烧和二次球磨的组合工艺,解决了传统固相法制备钛酸钡时反应不完全、纯度低,原料混合均匀性差以及高温煅烧后粒径粗大、团聚严重等问题,有助于获得纯度高、粒径均匀且四方相含量高的钛酸钡粉体,优化产品的介电性能和绝缘电阻率;此外,该制备方法工艺简单,成本低廉,设备要求低,可直接对接现有固相法生产线,易于实现工业化大规模生产,具有重要的工业应用价值
本申请以纳米级锐钛矿型二氧化钛为钛源,在无需额外添加矿化剂的条件下,通过与钡源进行一次球磨混合、分段煅烧和二次球磨的组合工艺,解决了传统固相法制备钛酸钡时反应不完全、纯度低,原料混合均匀性差以及高温煅烧后粒径粗大、团聚严重等问题,有助于获得纯度高、粒径均匀且四方相含量高的钛酸钡粉体,优化产品的介电性能和绝缘电阻率;此外,该制备方法工艺简单,成本低廉,设备要求低,可直接对接现有固相法生产线,易于实现工业化大规模生产,具有重要的工业应用价值。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application belongs to the field of inorganic non-metallic material preparation technology, specifically relating to a tetragonal barium titanate powder, its preparation method, and its application. Background Technology
[0002] Barium titanate (BaTiO3) is a typical ABO3-type perovskite ferroelectric material with excellent dielectric, ferroelectric, piezoelectric, and pyroelectric properties. It is one of the most widely used basic materials in the electronic ceramics industry and is known as the "pillar of electronic ceramics." With the development of electronic components towards miniaturization, multilayering, and high capacity, increasingly higher requirements are being placed on the purity, particle size, crystal form, and dispersibility of barium titanate powder.
[0003] Currently, the main methods for preparing barium titanate powder include solid-state method, hydrothermal method, co-precipitation method, and sol-gel method. Among them, the solid-state method was the first to achieve industrialized production, and it has advantages such as short process flow, simple equipment, low raw material cost, and ease of large-scale production. It remains the mainstream method for industrial production of barium titanate powder. The traditional solid-state method uses barium carbonate (BaCO3) and titanium dioxide (TiO2) as raw materials, which are mixed by ball milling and then calcined at high temperature to generate barium titanate through solid-state diffusion reaction.
[0004] Traditional solid-state methods have the following drawbacks: First, the raw material mixing is uneven, the reaction is incomplete, and unreacted BaCO3 or TiO2 impurities are easily left behind. Second, the calcination temperature is high (usually above 1200℃) and the holding time is long, leading to severe agglomeration of powder particles, large particle size, and uneven distribution, typically at the micrometer level. Third, high-temperature calcination easily causes the transformation of the tetragonal phase to the cubic phase, affecting the dielectric properties of the product. To obtain nano-sized barium titanate powder, long-term high-intensity ball milling is often required, but this easily introduces impurities from the grinding media, reducing the purity of the powder.
[0005] To address the shortcomings of solid-state methods, existing technologies include using nano-TiO2 as a raw material, adding mineralizers, or employing mechanochemical activation. For example, using nano-titanium dioxide and barium carbonate as raw materials, and adding lithium fluoride as a mineralizer, barium titanate powder is prepared by calcination at 900-1000℃. However, the introduction of mineralizers increases impurity content and affects the electrical properties of the product. Other technologies employ high-energy ball milling for mechanical activation to lower the calcination temperature, but high-energy ball milling equipment is expensive and easily introduces more impurities.
[0006] Therefore, developing a method for preparing barium titanate powder that is simple in process, low in cost, produces high-purity products with uniform particle size and high tetragonal phase content is an urgent technical problem to be solved. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this application aims to provide a tetragonal barium titanate powder, its preparation method, and its applications. This application uses nano-sized anatase titanium dioxide as the titanium source. Without the need for additional mineralizers, it employs a combined process of primary ball milling, staged calcination, and secondary ball milling with a barium source. This process solves the problems of incomplete reaction, low purity, poor raw material mixing uniformity, and large particle size and severe agglomeration after high-temperature calcination in traditional solid-state barium titanate preparation methods. This helps to obtain barium titanate powder with high purity, uniform particle size, and high tetragonal phase content, optimizing the product's dielectric properties and insulation resistivity. Furthermore, this preparation method is simple, low-cost, and requires minimal equipment. It can be directly integrated into existing solid-state production lines, facilitating large-scale industrial production and possessing significant industrial application value.
[0008] To achieve this objective, the present application adopts the following technical solution: In a first aspect, this application provides a method for preparing tetragonal barium titanate powder, the method comprising the following steps: Anatase titanium dioxide, barium salt, dispersant and solvent are ball-milled in one step to obtain a mixed slurry.
[0009] The mixed slurry was dried to obtain tetragonal barium titanate precursor powder.
[0010] The tetragonal barium titanate precursor powder is subjected to segmented calcination to obtain calcined products; the segmented calcination includes at least a first-stage calcination and a second-stage calcination with sequentially increasing temperatures.
[0011] The calcined product was subjected to secondary ball milling to obtain the tetragonal barium titanate powder.
[0012] This application uses nano-sized anatase titanium dioxide as the titanium source. Without the need for additional mineralizers, it employs a combined process of primary ball milling, staged calcination, and secondary ball milling with a barium source. This process solves the problems of incomplete reaction, low purity, poor raw material mixing uniformity, and large particle size and severe agglomeration after high-temperature calcination in traditional solid-state barium titanate preparation methods. It helps to obtain barium titanate powder with high purity, uniform particle size, and high tetragonal phase content, thus optimizing the product's dielectric properties and insulation resistivity. Furthermore, this preparation method is simple, low-cost, and requires minimal equipment. It can be directly integrated into existing solid-state production lines, facilitating large-scale industrial production and possessing significant industrial application value.
[0013] In this application, anatase titanium dioxide and barium salt are used as raw materials. A dispersant-assisted ball milling process is used to achieve nanoscale uniform mixing of barium titanium raw materials. Combined with a segmented calcination process and a secondary ball milling process, the dispersibility is improved. High-purity tetragonal phase barium titanate powder can be directly produced without the addition of additional mineralizers. This overcomes the shortcomings of traditional solid-state calcination methods, such as high calcination temperature, low product purity, insufficient tetragonal phase content, and difficulty in controlling particle size. It can also be easily realized for large-scale industrial production.
[0014] In this application, a segmented calcination process is adopted, which results in a more complete reaction and more controllable agglomeration; at the same time, no additional mineralizer is required, avoiding the introduction of impurity ions, which is conducive to improving the dielectric properties and insulation resistivity of the product.
[0015] In some embodiments, the average particle size of the anatase titanium dioxide is 60-150 nm, for example, it can be 60 nm, 80 nm, 100 nm, 125 nm or 150 nm.
[0016] In some embodiments, the specific surface area of the barium salt is 5-15 m². 2 / g, for example, could be 5m 2 / g, 7.5m 2 / g, 10m 2 / g, 12.5m 2 / g or 15m 2 / g, etc. It should be noted that the specific surface area can be obtained by nitrogen adsorption BET method.
[0017] In this application, the specific surface area is as low as 5-15m². 2 The combination of barium salts of a certain size with anatase titanium dioxide effectively increases the reaction contact area and provides more nucleation sites, thereby improving the solid-phase reaction rate. This results in barium titanate powder with small particle size, good dispersibility, and high tetragonality (c / a value) while lowering the calcination temperature. Furthermore, the synergistic matching of raw material particle size and specific surface area helps improve the uniformity of product particle size distribution. If the specific surface area of the barium salt is too large, the particle surface energy will be too high, leading to agglomeration during ball milling and uneven dispersion, thus reducing the uniformity of powder particle size distribution. Simultaneously, excessively high surface activity can cause overly vigorous reactions during calcination, ultimately degrading the tetragonality and dielectric properties of the barium titanate powder.
[0018] In some embodiments, the barium salt includes any one or a combination of at least two of barium carbonate, barium chloride, and barium hydroxide octahydrate.
[0019] In some embodiments, the barium-titanium molar ratio of the barium salt and anatase titanium dioxide is (0.98-1.02):1, for example, it can be 0.98:1, 0.99:1, 1.00:1, 1.01:1 or 1.02:1, etc.
[0020] In some embodiments, the primary ball milling method includes wet ball milling, and the conditions for wet ball milling include at least one of the following: The ball-to-material mass ratio is (3-6):1, for example, it can be 3:1, 4:1, 5:1 or 6:1, etc.; the material-to-liquid mass ratio is 1:(1.5-3), for example, it can be 1:1.5, 1:2.0, 1:2.5 or 1:3.0, etc.; the ball milling speed is 200-300 rpm, for example, it can be 200 rpm, 220 rpm, 250 rpm, 280 rpm or 300 rpm, etc.; the ball milling time is 12-36 h, for example, it can be 12 h, 18 h, 24 h, 30 h or 36 h, etc.
[0021] This application employs a wet ball milling process with the above process parameters, and in conjunction with the use of a dispersant, it can achieve nano-uniform mixing of titanium barium raw materials.
[0022] It should be noted that the ball-to-material mass ratio refers to the mass ratio of the ball milling media to the solid material, while the material-to-liquid mass ratio refers to the mass ratio of the solid material to the liquid medium (solvent).
[0023] In some embodiments, the secondary ball milling method includes wet ball milling, and the conditions for wet ball milling include at least one of the following: The ball-to-material mass ratio is (3-6):1, for example, it can be 3:1, 4:1, 5:1 or 6:1, etc.; the ball milling speed is 200-300 rpm, for example, it can be 200 rpm, 220 rpm, 250 rpm, 280 rpm or 300 rpm, etc.; the ball milling time is 6-18h, for example, it can be 6h, 8h, 10h, 12h, 14h, 16h or 18h, etc.
[0024] The wet ball milling of the above-mentioned process parameters of the present invention, followed by secondary ball milling, is beneficial for breaking up soft agglomerates, preparing highly stable slurries, and reducing subsequent molding defects. Furthermore, in conjunction with primary ball milling, it can better narrow the particle size distribution, eliminate coarse particles, and ensure uniform and consistent product performance.
[0025] In some embodiments, the dispersant includes polyvinylpyrrolidone and / or polyethylene glycol.
[0026] In some embodiments, the mass content of the dispersant is 0.5-2 wt%, based on the total mass of the anatase titanium dioxide and barium salt, for example, it can be 0.5 wt%, 0.8 wt%, 1.0 wt%, 1.5 wt%, or 2.0 wt%.
[0027] In some embodiments, the atmosphere for the segmented calcination includes an air atmosphere.
[0028] In some embodiments, the calcination temperature is 600-800℃, for example, 600℃, 650℃, 700℃, 750℃ or 800℃, and the holding time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h or 3h.
[0029] This application involves a calcination process at 600-800℃ to remove volatile impurities such as moisture and organic additives, avoid carbon residue and subsequent calcination defects, complete the initial volume change in advance, and reduce the risk of cracking and deformation of the green body during subsequent high-temperature calcination.
[0030] In some embodiments, the temperature of the second-stage calcination is 1000-1200℃, for example, 1000℃, 1050℃, 1100℃, 1150℃ or 1200℃, and the holding time is 2-6h, for example, 2h, 3h, 4h, 5h or 6h.
[0031] This application involves a two-stage calcination process at 1000-1200℃. The purpose is to allow the incompletely reacted BaCO3 and TiO2 after pre-calcination to undergo a full solid-phase diffusion reaction, completely transforming them into BaTiO3, eliminating raw material residues, and obtaining pure-phase barium titanate powder.
[0032] In some embodiments, the heating rate from the first stage of calcination to the second stage of calcination is 3-8℃ / min, for example, it can be 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min or 8℃ / min, etc.
[0033] In the process of heating from the first stage of calcination to the second stage of calcination, this application controls the heating rate to be 3-8℃ / min, which can better prevent the rapid formation of a dense BaTiO3 shell on the particle surface and block the diffusion reaction of BaCO3 and TiO2 inside, thus creating a "wrapping effect". This allows the raw materials to react fully, reduces residues, and obtains pure phase barium titanate.
[0034] In some embodiments, both the atmosphere of the first-stage calcination and the atmosphere of the second-stage calcination contain CO2, and the partial pressure of CO2 in the atmosphere of the first-stage calcination is greater than the partial pressure of CO2 in the atmosphere of the second-stage calcination.
[0035] In some embodiments, the partial pressure of CO2 in the calcination atmosphere is 0.05-0.25 MPa, for example, it can be 0.05 MPa, 0.10 MPa, 0.15 MPa, 0.20 MPa or 0.25 MPa.
[0036] In some embodiments, the partial pressure of CO2 in the atmosphere of the two-stage calcination is ≤0.01MPa, for example, it can be 0.001MPa, 0.003MPa, 0.005MPa, 0.008MPa or 0.01MPa, etc.
[0037] In this application, introducing CO2 at a suitable partial pressure during the first stage of calcination can inhibit the premature decomposition of barium salts (such as barium carbonate) and the resulting volatilization and loss of barium components, thereby reducing the formation of impurity phases. During the second stage of calcination, using an air atmosphere with a low CO2 partial pressure is beneficial for the forward solid-phase reaction, resulting in high-purity tetragonal barium titanate powder.
[0038] In some embodiments, the preparation method includes the following steps: (1) Weigh anatase titanium dioxide and barium carbonate according to a barium-titanium molar ratio of (0.98-1.02):1, add ball milling media, solvent (e.g., anhydrous ethanol) and dispersant, and perform a single wet ball milling to obtain a mixed slurry; The anatase titanium dioxide has an average particle size of 60-150 nm; the barium carbonate has a specific surface area of 5-15 m². 2 / g; the wet ball milling conditions include: a ball-to-material mass ratio of (3-6):1, a material-to-liquid mass ratio of 1:(1.5-3), a ball milling speed of 200-300 rpm, and a ball milling time of 12-36 h; the dispersant includes polyvinylpyrrolidone and / or polyethylene glycol; based on the total mass of the anatase titanium dioxide and barium carbonate, the mass content of the dispersant is 0.5-2 wt%; (2) The mixed slurry is dried at 80-120℃ (e.g., 80℃, 90℃, 100℃, 110℃ or 120℃, etc.) for 6-12 hours (e.g., 6 hours, 8 hours, 10 hours or 12 hours, etc.), ground and passed through a 200-300 mesh sieve (e.g., 200 mesh, 220 mesh, 240 mesh, 260 mesh, 280 mesh or 300 mesh, etc.) to obtain tetragonal barium titanate precursor powder; (3) In an air atmosphere, the tetragonal barium titanate precursor powder is first calcined at 600-800℃ for 1-3 hours, and then heated to 1000-1200℃ at a heating rate of 3-8℃ / min for 2-6 hours for a second stage of calcination, followed by cooling to obtain the calcined product. (4) The calcined product is subjected to secondary wet ball milling, dried at 80-120℃ (e.g., 80℃, 90℃, 100℃, 110℃ or 120℃, etc.) and then passed through a 300-400 mesh sieve (e.g., 300 mesh, 320 mesh, 340 mesh, 360 mesh, 380 mesh or 400 mesh, etc.) to obtain the tetragonal barium titanate powder; The conditions for the secondary wet ball milling include: a ball-to-material mass ratio of (3-6):1; a ball milling speed of 200-300 rpm; and a ball milling time of 6-18 h.
[0039] Secondly, this application provides a tetragonal barium titanate powder, which is prepared by the preparation method described in the first aspect.
[0040] In some embodiments, the purity of the tetragonal barium titanate powder is ≥99%, for example, it can be 99.0%, 99.2%, 99.5%, 99.8%, or 99.9%. It should be noted that the purity can be obtained by inductively coupled plasma optical emission spectrometry (ICP-OES).
[0041] In some embodiments, the tetragonal c / a value of the barium titanate powder is ≥1.008, for example, it can be 1.008, 1.010, 1.012, 1.015, or 1.020. It should be noted that the tetragonal c / a value can be obtained by X-ray diffraction (XRD). Specifically, X-ray diffraction analysis is performed on the barium titanate powder, and the lattice constants a and c are calculated by full-spectrum fitting; the ratio of the two is the c / a value.
[0042] In some embodiments, the average particle size of the tetragonal barium titanate powder is 200-500 nm, for example, it can be 200 nm, 250 nm, 300 nm, 400 nm, or 500 nm. It should be noted that the average particle size can be obtained by laser diffraction scattering.
[0043] Thirdly, this application provides an application of the tetragonal barium titanate powder as described in the second aspect in the fields of multilayer ceramic capacitors, thermistors, ferroelectric and piezoelectric devices.
[0044] The numerical range described in this application includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values included in the range.
[0045] Compared with the prior art, this application has the following advantages: This application uses nano-sized anatase titanium dioxide as the titanium source. Without the need for additional mineralizers, it employs a combined process of primary ball milling, staged calcination, and secondary ball milling with a barium source. This process solves the problems of incomplete reaction, low purity, poor raw material mixing uniformity, and large particle size and severe agglomeration after high-temperature calcination in traditional solid-state barium titanate preparation methods. It helps to obtain barium titanate powder with high purity, uniform particle size, and high tetragonal phase content, thus optimizing the product's dielectric properties and insulation resistivity. Furthermore, this preparation method is simple, low-cost, and requires minimal equipment. It can be directly integrated into existing solid-state production lines, facilitating large-scale industrial production and possessing significant industrial application value. Detailed Implementation
[0046] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.
[0047] The scope of this application can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form a valid range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this application. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this application. In this application, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0048] In this application, "at least two combinations" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or at least two combinations" means any one of the listed items, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this application. In this application, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this application, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.
[0049] In this application, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond those listed unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this application, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this application. The term "embodiment" as used in this application means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in this application can be combined with other embodiments that do not conflict with existing technologies. The ordinal numbers "first," "second," "third," and "fourth," etc., used in this application in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect," are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.
[0050] In this application, the order in which the steps are written in the methods described in the various embodiments does not imply a strict execution order. The actual execution order of each step should be determined according to its function and possible internal logic. Unless otherwise specified, all steps in this application can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.
[0051] Example 1 This embodiment provides a method for preparing tetragonal barium titanate powder, the preparation method comprising the following steps: (1) Weigh anatase titanium dioxide and barium carbonate at a barium-titanium molar ratio of 1:1, add zirconium oxide balls, anhydrous ethanol and polyvinylpyrrolidone and perform a single wet ball milling to obtain a mixed slurry.
[0052] The anatase titanium dioxide has an average particle size of 100 nm; the barium carbonate has a specific surface area of 10 m². 2 / g; The conditions for wet ball milling include: a ball-to-material mass ratio of 5:1, a material-to-liquid mass ratio of 1:2, a ball milling speed of 250 rpm, and a ball milling time of 24 h; Based on the total mass of the anatase titanium dioxide and barium carbonate, the mass content of the polyvinylpyrrolidone is 1 wt%.
[0053] (2) The mixed slurry was dried at 100°C for 8 hours, ground and passed through a 250-mesh sieve to obtain tetragonal barium titanate precursor powder.
[0054] (3) In an air atmosphere, the tetragonal barium titanate precursor powder is first calcined to 700°C at a heating rate of 5°C / min for 2 hours, and then calcined to 1100°C at a heating rate of 5°C / min for 4 hours. After cooling, the calcined product is obtained.
[0055] (4) The calcined product is subjected to secondary wet ball milling, dried at 100°C and passed through a 325-mesh sieve to obtain the tetragonal barium titanate powder.
[0056] The conditions for the secondary wet ball milling include: the liquid medium is anhydrous ethanol, the ball-to-material mass ratio is 4:1, the ball milling speed is 250 rpm, and the ball milling time is 12 h.
[0057] This embodiment also provides a tetragonal barium titanate powder, which is prepared by the preparation method described above.
[0058] The purity of the tetragonal barium titanate powder is 99.2%.
[0059] The tetragonal c / a value of the tetragonal barium titanate powder is 1.009.
[0060] The average particle size of the tetragonal barium titanate powder is 300 nm.
[0061] Example 2 This embodiment provides a method for preparing tetragonal barium titanate powder, the preparation method comprising the following steps: (1) Weigh anatase titanium dioxide and barium carbonate at a barium-titanium molar ratio of 0.98:1, add zirconium oxide balls, anhydrous ethanol and polyvinylpyrrolidone and perform a single wet ball milling to obtain a mixed slurry.
[0062] The anatase titanium dioxide has an average particle size of 60 nm; the barium carbonate has a specific surface area of 5 m². 2 / g; The conditions for wet ball milling include: a ball-to-material mass ratio of 3:1, a material-to-liquid mass ratio of 1:1.5, a ball milling speed of 200 rpm, and a ball milling time of 12 h; Based on the total mass of the anatase titanium dioxide and barium carbonate, the mass content of the polyvinylpyrrolidone is 0.5 wt%.
[0063] (2) The mixed slurry was dried at 80°C for 12 hours, ground, and passed through a 200-mesh sieve to obtain tetragonal barium titanate precursor powder.
[0064] (3) In an air atmosphere, the tetragonal barium titanate precursor powder is first calcined to 600°C at a heating rate of 3°C / min for 3 hours, and then calcined to 1000°C at a heating rate of 3°C / min for 6 hours. After cooling, the calcined product is obtained.
[0065] (4) The calcined product is subjected to secondary wet ball milling, dried at 80°C and passed through a 300-mesh sieve to obtain the tetragonal barium titanate powder.
[0066] The conditions for the secondary wet ball milling include: the liquid medium is anhydrous ethanol, the ball-to-material mass ratio is 3:1, the ball milling speed is 200 rpm, and the ball milling time is 6 h.
[0067] This embodiment also provides a tetragonal barium titanate powder, which is prepared by the preparation method described above.
[0068] The purity of the tetragonal barium titanate powder is 99.1%.
[0069] The tetragonal c / a value of the tetragonal barium titanate powder is 1.008.
[0070] The average particle size of the tetragonal barium titanate powder is 500 nm.
[0071] Example 3 This embodiment provides a method for preparing tetragonal barium titanate powder, the preparation method comprising the following steps: (1) Weigh anatase titanium dioxide and barium carbonate at a barium-titanium molar ratio of 1.02:1, add zirconium oxide balls, anhydrous ethanol and polyvinylpyrrolidone and perform a single wet ball milling to obtain a mixed slurry.
[0072] The anatase titanium dioxide has an average particle size of 150 nm; the barium carbonate has a specific surface area of 15 m². 2 / g; The conditions for wet ball milling include: a ball-to-material mass ratio of 6:1, a material-to-liquid mass ratio of 1:3, a ball milling speed of 300 rpm, and a ball milling time of 36 h; Based on the total mass of the anatase titanium dioxide and barium carbonate, the mass content of the polyvinylpyrrolidone is 2 wt%.
[0073] (2) The mixed slurry was dried at 120°C for 6 hours, ground and passed through a 300-mesh sieve to obtain tetragonal barium titanate precursor powder.
[0074] (3) In an air atmosphere, the tetragonal barium titanate precursor powder is first calcined to 800°C at a heating rate of 8°C / min for 4 hours, and then calcined to 1200°C at a heating rate of 8°C / min for 2 hours. After cooling, the calcined product is obtained.
[0075] (4) The calcined product is subjected to secondary wet ball milling, dried at 120°C and passed through a 400-mesh sieve to obtain the tetragonal barium titanate powder.
[0076] The conditions for the secondary wet ball milling include: the liquid medium is anhydrous ethanol, the ball-to-material mass ratio is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 18 h.
[0077] This embodiment also provides a tetragonal barium titanate powder, which is prepared by the preparation method described above.
[0078] The purity of the tetragonal barium titanate powder is 99.3%.
[0079] The tetragonal c / a value of the tetragonal barium titanate powder is 1.01.
[0080] The average particle size of the tetragonal barium titanate powder is 400 nm.
[0081] Example 4 The difference between this embodiment and Embodiment 1 is that the air atmosphere in both the first-stage calcination and the second-stage calcination contains CO2, and the partial pressure of CO2 in the air atmosphere of the first-stage calcination is greater than that in the air atmosphere of the second-stage calcination; the partial pressure of CO2 in the air atmosphere of the first-stage calcination is 0.15 MPa; and the partial pressure of CO2 in the air atmosphere of the second-stage calcination is 0.01 MPa.
[0082] The remaining preparation methods and parameters are consistent with those in Example 1.
[0083] Example 5 The difference between this embodiment and Embodiment 1 is that the specific surface area of the barium carbonate is 20 m². 2 / g.
[0084] The remaining preparation methods and parameters are consistent with those in Example 1.
[0085] Example 6 The difference between this embodiment and Embodiment 1 is that the calcination temperature of the first section is 500°C.
[0086] The remaining preparation methods and parameters are consistent with those in Example 1.
[0087] Example 7 The difference between this embodiment and Embodiment 1 is that the calcination temperature of the first section is 900°C.
[0088] The remaining preparation methods and parameters are consistent with those in Example 1.
[0089] Example 8 The difference between this embodiment and Embodiment 1 is that the heating rate from the first stage of calcination to the second stage of calcination is 10℃ / min.
[0090] The remaining preparation methods and parameters are consistent with those in Example 1.
[0091] Example 9 The difference between this embodiment and Embodiment 1 is that the temperature of the two-stage calcination is 1300℃.
[0092] The remaining preparation methods and parameters are consistent with those in Example 1.
[0093] Comparative Example 1 The difference between this comparative example and Example 1 is that the anatase titanium dioxide is replaced with rutile micron-sized titanium dioxide with an average particle size of 1 μm.
[0094] The remaining preparation methods and parameters are consistent with those in Example 1.
[0095] X-ray diffraction analysis of the barium titanate powder prepared in this comparative example showed that the product contained a large amount of unreacted BaCO3 and TiO2 impurities, indicating incomplete reaction and a purity of only 92.5%. Furthermore, the product was mainly cubic barium titanate with a low tetragonal phase content. This is because micron-sized rutile titanium dioxide has low reactivity and cannot complete the solid-phase reaction under the same calcination conditions.
[0096] Comparative Example 2 The difference between this comparative example and Example 1 is that the polyvinylpyrrolidone is not added in step (1).
[0097] The remaining preparation methods and parameters are consistent with those in Example 1.
[0098] X-ray diffraction analysis of the barium titanate powder prepared in this comparative example showed that the purity of the product was only 98.2%, containing a small amount of impurity phase; the powder particles were severely agglomerated, with an average particle size of about 800 nm and poor dispersibility. This was due to the lack of dispersant, which caused the nano-titanium dioxide to agglomerate during ball milling, resulting in uneven mixing of raw materials and insufficient reaction. At the same time, the agglomeration was aggravated after calcination.
[0099] Comparative Example 3 The difference between this comparative example and Example 1 is that in step (3), no first-stage calcination is performed, only second-stage calcination is performed.
[0100] The remaining preparation methods and parameters are consistent with those in Example 1.
[0101] Comparative Example 4 The difference between this comparative example and Example 1 is that a second wet ball milling is not performed in step (4).
[0102] The remaining preparation methods and parameters are consistent with those in Example 1.
[0103] Performance testing The barium titanate powders provided in the above embodiments and comparative examples were subjected to the following tests: 1) Purity test; 2) Tetragonal phase c / a value test; 3) Average particle size test.
[0104] The test results are shown in Table 1.
[0105] Table 1 analyze: As shown in Table 1, the method for preparing tetragonal barium titanate powder provided by this invention uses nano-sized anatase titanium dioxide and barium carbonate as raw materials. The raw materials are uniformly mixed through wet ball milling with a dispersant. A segmented calcination process promotes complete solid-phase reaction, and secondary ball milling improves dispersibility. Without adding a mineralizing agent, barium titanate powder with a purity ≥99.0%, a tetragonal c / a value ≥1.008, and an average particle size of 200-500 nm is prepared. This method is simple, low-cost, and easy to industrialize. The resulting product has excellent performance and can be widely used in electronic components such as multilayer ceramic capacitors.
[0106] As can be seen from the comparison between Example 1 and Example 5, if the specific surface area of barium carbonate is too large, it will cause powder agglomeration, poor processing and molding, uncontrolled synthesis and sintering, and decreased storage stability, which has a significant impact on the preparation of electronic ceramics such as MLCC.
[0107] A comparison of Examples 1 and 6-7 shows that if the calcination temperature of the first stage is too low, the precursor decomposition and crystallization development will be insufficient, resulting in more impurities; the specific surface area of the powder will be too high, making it prone to agglomeration and reducing processability; subsequent synthesis reactions will be prone to uneven and uncontrolled reactions; if the calcination temperature of the first stage is too high, the grains will grow excessively, the specific surface area will drop sharply, and the reactivity will be insufficient; the particles will be prone to sintering and sticking together to form hard agglomerates.
[0108] As can be seen from the comparison between Example 1 and Example 8, if the heating rate from the first stage of calcination to the second stage of calcination is too high, problems such as uncontrolled decomposition and impurity removal, uneven grain development, and aggravated hard agglomeration will occur due to uneven heat conduction of the powder, resulting in a decrease in powder purity, specific surface area and processing performance. At the same time, it will affect the quality of downstream barium titanate synthesis and the performance consistency and service life of MLCC products.
[0109] As can be seen from the comparison between Example 1 and Example 9, if the temperature of the second-stage calcination is too high, it will cause excessive sintering growth of barium carbonate grains, a sharp drop in specific surface area, insufficient reactivity, and it is also easy to form severe hard agglomerates and lumps.
[0110] As can be seen from the comparison between Example 1 and Comparative Example 1, if anatase titanium dioxide is replaced with rutile micron-sized titanium dioxide, the product contains more unreacted BaCO3 and TiO2 impurities, the reaction is incomplete, and the purity is low; moreover, it is mainly cubic barium titanate with low tetragonal phase content.
[0111] As can be seen from the comparison between Example 1 and Comparative Example 2, if the polyvinylpyrrolidone is not added in step (1), the purity of the product is only 98.2%, and it contains a small amount of impurities; the powder particles are severely agglomerated, with an average particle size of about 800 nm and poor dispersibility. This is because the lack of dispersant causes the nano-titanium dioxide to agglomerate during the ball milling process, resulting in uneven mixing of raw materials and insufficient reaction. At the same time, the agglomeration is aggravated after calcination.
[0112] As can be seen from the comparison between Example 1 and Comparative Example 3, if only two-stage calcination is performed instead of the first-stage calcination in step (3), problems such as incomplete removal of impurities, loss of control over crystal form and grain size, and aggravated hard agglomeration will occur due to the lack of precursor decomposition buffer and preliminary crystallization process.
[0113] As can be seen from the comparison between Example 1 and Comparative Example 4, if secondary wet ball milling is not performed in step (4), the powder particle size will be coarser, the distribution will be wider, and the agglomeration will be intensified, which will deteriorate the slurry performance and the final product quality.
[0114] It should be noted that this application illustrates the process method through the above embodiments, but this application is not limited to the above process steps, that is, it does not mean that this application must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to this application, equivalent substitutions of the raw materials used in this application, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of this application.
Claims
1. A method for preparing tetragonal barium titanate powder, characterized in that, The preparation method includes the following steps: Anatase titanium dioxide, barium salt, dispersant and solvent are ball-milled in one step to obtain a mixed slurry; The mixed slurry was dried to obtain tetragonal barium titanate precursor powder; The tetragonal barium titanate precursor powder is subjected to segmented calcination to obtain calcined products; the segmented calcination includes at least a first-stage calcination and a second-stage calcination with sequentially increasing temperatures. The calcined product was subjected to secondary ball milling to obtain the tetragonal barium titanate powder.
2. The preparation method according to claim 1, characterized in that, The anatase titanium dioxide has an average particle size of 60-150 nm. And / or, the specific surface area of the barium salt is 5-15 m². 2 / g; And / or, the barium salt includes any one or a combination of at least two of barium carbonate, barium chloride, and barium hydroxide octahydrate; And / or, the barium-titanium molar ratio of the barium salt and anatase titanium dioxide is (0.98-1.02):
1.
3. The preparation method according to claim 1 or 2, characterized in that, The ball milling method includes wet ball milling, and the conditions for wet ball milling include at least one of the following: The ball-to-material mass ratio is (3-6):1; the material-to-liquid mass ratio is 1:(1.5-3); the ball mill speed is 200-300 rpm; and the ball milling time is 12-36 h. And / or, the secondary ball milling method includes wet ball milling, and the conditions for wet ball milling include at least one of the following: The ball-to-material mass ratio is (3-6):1; the ball mill speed is 200-300 rpm; and the ball milling time is 6-18 h.
4. The preparation method according to any one of claims 1-3, characterized in that, The dispersant includes polyvinylpyrrolidone and / or polyethylene glycol; And / or, based on the total mass of the anatase titanium dioxide and barium salt, the mass content of the dispersant is 0.5-2 wt%.
5. The preparation method according to any one of claims 1-4, characterized in that, The atmosphere for the segmented calcination includes an air atmosphere; And / or, the calcination temperature of the first stage is 600-800℃, and the holding time is 1-3h; And / or, the temperature of the two-stage calcination is 1000-1200℃, and the holding time is 2-6h; And / or, the heating rate from the first stage of calcination to the second stage of calcination is 3-8℃ / min.
6. The preparation method according to claim 5, characterized in that, Both the first-stage calcination and the second-stage calcination atmospheres contain CO2, and the partial pressure of CO2 in the first-stage calcination atmosphere is greater than the partial pressure of CO2 in the second-stage calcination atmosphere. And / or, in the calcination atmosphere, the partial pressure of CO2 is 0.05-0.25 MPa; And / or, in the atmosphere of the two-stage calcination, the partial pressure of CO2 is ≤0.01MPa.
7. The preparation method according to any one of claims 1-6, characterized in that, The preparation method includes the following steps: (1) Weigh anatase titanium dioxide and barium carbonate at a barium-titanium molar ratio of (0.98-1.02):1, add ball milling media, solvent and dispersant and perform wet ball milling once to obtain a mixed slurry; The anatase titanium dioxide has an average particle size of 60-150 nm; the barium carbonate has a specific surface area of 5-15 m². 2 / g; the wet ball milling conditions include: a ball-to-material mass ratio of (3-6):1, a material-to-liquid mass ratio of 1:(1.5-3), a ball milling speed of 200-300 rpm, and a ball milling time of 12-36 h; the dispersant includes polyvinylpyrrolidone and / or polyethylene glycol; based on the total mass of the anatase titanium dioxide and barium carbonate, the mass content of the dispersant is 0.5-2 wt%; (2) The mixed slurry is dried at 80-120℃ for 6-12h, ground and passed through a 200-300 mesh sieve to obtain tetragonal barium titanate precursor powder; (3) In an air atmosphere, the tetragonal barium titanate precursor powder is first calcined at 600-800℃ for 1-3 hours, and then heated to 1000-1200℃ at a heating rate of 3-8℃ / min for 2-6 hours for a second stage of calcination, followed by cooling to obtain the calcined product. (4) The calcined product is subjected to secondary wet ball milling, dried at 80-120℃ and passed through a 300-400 mesh sieve to obtain the tetragonal barium titanate powder; The conditions for the secondary wet ball milling include: a ball-to-material mass ratio of (3-6):1; a ball milling speed of 200-300 rpm; and a ball milling time of 6-18 h.
8. A tetragonal barium titanate powder, characterized in that, The tetragonal barium titanate powder is prepared by the preparation method described in any one of claims 1-7.
9. The tetragonal barium titanate powder according to claim 8, characterized in that, The purity of the tetragonal barium titanate powder is ≥99%; And / or, the tetragonal c / a value of the tetragonal barium titanate powder is ≥1.008; And / or, the average particle size of the tetragonal barium titanate powder is 200-500 nm.
10. An application of the tetragonal barium titanate powder as described in claim 8 or 9 in the fields of multilayer ceramic capacitors, thermistors, ferroelectric and piezoelectric devices.